Molecular basis of genetic plasticity to varying environmental conditions on growing rice by dry/direct-sowing and exposure to drought stress: Insights for DSR varietal development - Kumar, Suresh; Kumar, Santosh; Krishnan, Gopala S.; Mohapatra, Trilochan (Frontiers in Plant Science, 2022)
Rice requires plenty of water for its cultivation by transplanting. This poses several challenges to its cultivation due to erratic rainfall resulting in drought, flood, and other abiotic stresses of varying intensity. Dry/direct-sown rice (DSR) has emerged as a water-saving/climate-smart alternative to transplanted rice (TPR). The performance of a rice cultivar on growing by different methods of planting under varying environmental conditions varies considerably. However, the molecular basis of the observed phenotypic plasticity of rice to varying environmental conditions is still elusive. Resilience to various environmental fluctuations is important to ensure sustainable rice production in the present era of global climate change. Our observations on exclusively up-regulated genes in leaf of Nagina 22 (N 22) grown by dry/direct-sowing and subjected to drought stress at panicle initiation stage (compared to that in leaf of IR 64), and another set of genes exclusively down-regulated in leaf of N 22 (compared to that in leaf of IR 64) indicate important roles of leaf in stress resilience. A large number of genes down-regulated exclusively in root of N 22 on dry/direct-sowing subjected to drought stress indicates a major contribution of roots in stress tolerance. The genes for redox-homeostasis, transcription factors, stress signaling, carbohydrate metabolism, and epigenetic modifications play important roles in making N 22 better adapted to DSR conditions. More importantly, the involvement of genes in rendering genetic plasticity to N 22 under changing environmental conditions was confirmed by reversal of the method of planting. To the best of our knowledge, this is the first report on decoding the molecular basis of genetic plasticity of rice grown by two different methods of planting subjected to drought stress at the reproductive stage of plant growth. This might help in DSR varietal development program to enhance water-productivity, conserve natural resources, and minimize the emission of greenhouse gases, thus achieving the objectives of negative-emission agriculture.